Tinjauan Psikologis Pemerolehan Bahasa dan Kemampuan Bernalar Pada Anak - Pateda, Lamsike (IAIN Sultan Amai Gorontalo, 2015)
The parents and the family have important role in educating and delivering children to acquire their language. The process of childrenâ language acquisition is known as golden age phase, it is the important phase of human life. The success of development phase is determined here, because the childrenâ brain develop faster than the adult and it influences to their stimulus which come from their envronment, either in home or in school. Eventually, the children will have well knowledge according to previous information then connecting to the next information. The acquisition and the using of language (the ability of thinking) shows the children comprehension toward word/language meaning which basically depend on sense rasio and physical data.